Capacity Development in an Undergraduate Nursing Program in Vietnam - Kang, Sunjoo; Ho, Thi Thuy Trang; Nguyen, Thi Anh Phuong (Frontiers in Public Health, 2018)
Background: Nurses are an essential human resource to ensure a healthy population and support the socio-economic development. However, little research has focused on the capacity development of nurses. Objective: The performance of a capacity development project for an undergraduate nursing program in Vietnam was reviewed to share lessons. Design: A descriptive case report Setting: A baccalaureate nursing program in Vietnam from June 2014 to June 2016 Methods: A case report was analyzed in terms of the project’s process, and the outcomes of two years’ activities were evaluated. Results: Practice-based curriculum redesign and two basic nursing subjects were developed after five rounds of curriculum workshops. To improve application efficiency, two nursing experts were dispatched to provide instructions regarding the application of the new subjects. Three candidates were invited to complete their master’s and doctoral studies in Korea. An advanced nursing education environment was supported with simulation labs equipped within a ubiquitous network. The result of experts’ evaluation was excellent by every criterion of the Organisation for Economic Co-operation and Development- Development Assistance Committee. Conclusions: The capacity development of a nursing program was possible through ownership, accountability, and results-based management. Gradual improvement in nursing academic and clinical capacity building based on research evidence can empower partner countries’ nursing leadership. Introduction